ANALISIS HUBUNGAN SANITASI TOTAL BERBASIS MASYRAKAT (STBM) DENGAN KEJADIAN DIARE PADA BALITA DI DESA SUKA MULIA KECAMATAN HINAI KABUPATEN LANGKAT - Novrika Silalahi; Rumiris Yulinar Sinambela; Sulastri Br Ginting (Jurnal Penelitian Kesmasy, 2020)
There was one death case happened in 2018-2019 at Puskesmas Hinai Kabupaten Langkat regency for under five years children that caused by diarrhea. Low clean and healthy behavior (36,9) and total sanitation are one of the causes. Good total sanitation can decrease 94% incidence of diarrhea. The purpose of the research was to determine the relationship between total sanitation with incidence of diarrhea for under five years children. The type of this research was cross sectional. The population of this research was all under five years children who live in suka mulia. The sample were 67 respondents. The instrument used questionnaire sheet. The result of this study that there were relationship between behavior defection (p= 0,0015), hand washing behavior (p= 0,006), rubbish treatment (p= 0,017), waste water treatment (p= 0,010), and there was no relationship of good and drinking water treatment with diarrhea for five years children (p= 0,804). The advice for society was to improve total sanitation in order not to be source or intermediaries of diarrhea. For related institution to give education about total sanitation to prevent diarrhea